The Adoption of Export as an Innovative Strategy - Lee, Woo-Young; Brasch, John J (Journal of International Business Studies, 1978)
This research identifies a typical form of the exporting adoption process regarding two dimensions—the initiating force and the rationality of the export adoption process. It was hypothesized, first, for this study that, in the export innovation adoption situation, the adoption process would be initiated more often by internally perceived problems or needs rather than by the passively received information about the innovation: exporting. A second major hypothesis took the view that the export adoption process was more rational than nonrational. Third, using various instruments—including Hage and Aiken's index—we measured the organizational structural characteristics of 35 Nebraska exporting manufacturers. The innovation-oriented and nonrational export adoption processes proved to be the more common in this group.